Perancangan User Experience Aplikasi Laporkan untuk Mempercepat Proses Laporan Kehilangan di Polsek Larangan - Ingke Ryastratika Milenia Efendi; Lutfi Fanani; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Larangan Sector Police is one of the police offices in Pamekasan Regency. In the Larangan Sector Police there is section of Integrated Police Service Center (SPKT) which is making a Loss Sign Certificate (SKTLK). There are three members of the SKTLK section with one person on duty every day, sometimes the community don't bring files completely causeing the process of SKTLK at the Larangan Sector Police to longer and causing queues. Besides that, the process of making SKTLK at the Larangan Sector Police is still done manually that can cause inefficient data search. Therefore, with the design of the user experience in the application of laporkan can provide a solution of making SKTLK at the Larangan Sector Police. The method used is the Design Thinking method which consists of the Empathize stage, Define, Ideate, Prototype, and Testing. Testing the design of the user experience in the application of laporkan using usability testing and User Experience Questionnaire (UEQ). The results of testing using usability testing consists of effectiveness aspect with result is 90,7%, efficiency aspect with result ranging from 0,3205 to 0,0266 goals/sec, and satisfaction aspect with the result is 83,5. The results of testing using UEQ from the aspect of attractiveness is 2,33, perspicuity is 2,09, efficiency is 2,30, dependability is 2,26, stimulation is 2,28, and novelty is 2,20.